Respuesta :
Answer:
[tex]x_1=5\\x_2=-3[/tex]
Step-by-step explanation:
You have the following quadratic equation given in the problem:
[tex]x^{2}-2x-3=12[/tex]
You must make the equation equal to zero, as following:
[tex]x^{2}-2x-3-12=0[/tex]
Add like terms:
[tex]x^{2}-2x-15=0[/tex]
Now, to factor the equation, you must find two numbers whose sum is -2 and whose product is -15. Therefore, you have:
[tex](x-5)(x+3)=0\\x_1=5\\x_2=-3[/tex]
Answer:
x = -3 and x = 5
Step-by-step explanation:
x² − 2x − 3 = 12
x² − 2x − 3 - 12 = 0
x² − 2x − 15 = 0
Product = -15
sum = -2
Factors are: 3, -5
So the equation becomes;
x² − 2x − 15 = 0
x² + 3x - 5x − 15 = 0
(x² + 3x) - (5x + 15) = 0
x(x + 3) - 5(x + 3) = 0
(x + 3)(x - 5) = 0
∴ (x + 3) = 0
x = -3
or
(x - 5) = 0
x = 5